The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3390/brainsci10010013
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Tendon-Evoked Reflex Is Increased in the Torque-Enhanced State Following Active Lengthening Compared to a Purely Isometric Contraction

Abstract: Residual torque enhancement (rTE) is a history-dependent property of muscle, which results in an increase in steady-state isometric torque production following an active lengthening contraction as compared to a purely isometric (ISO) contraction at the same muscle length and level of activation. Once thought to be only an intrinsic property of muscle, recent evidence during voluntary contractions indicates a neuromechanical coupling between motor neuron excitability and the contractile state of the muscle. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
(88 reference statements)
2
7
1
Order By: Relevance
“…During submaximal dorsiflexion contractions, Sypkes et al (2018) found unchanged TA MEPs, but reduced TA CMEPs, following active muscle stretch compared with fixed-end reference contractions. This is in line with the idea of reduced motor unit recruitment (Altenburg et al 2008) and might be caused by tension-related afferent feedback as assessed by tendon-evoked inhibitory reflexes (Contento et al 2019). Contrary to these findings under submaximal contraction intensities, Hahn et al (2012) found larger MEPs, but unchanged CMEPs, following stretch of the plantar flexors during maximal voluntary contractions.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…During submaximal dorsiflexion contractions, Sypkes et al (2018) found unchanged TA MEPs, but reduced TA CMEPs, following active muscle stretch compared with fixed-end reference contractions. This is in line with the idea of reduced motor unit recruitment (Altenburg et al 2008) and might be caused by tension-related afferent feedback as assessed by tendon-evoked inhibitory reflexes (Contento et al 2019). Contrary to these findings under submaximal contraction intensities, Hahn et al (2012) found larger MEPs, but unchanged CMEPs, following stretch of the plantar flexors during maximal voluntary contractions.…”
Section: Introductionsupporting
confidence: 88%
“…The unchanged MEP amplitudes and SP durations that we found in the presence of rFE compared with the reference contractions is in line with the findings of Sypkes et al (2018) and indicate that the overall corticospinal excitability was unaffected. However, unchanged MEPs do not exclude potential spinal modulations and the smaller CMEP amplitudes in the presence of rFE observed by Sypkes et al (2018) could be interpreted as reduced spinal motoneuron excitability, which might be due to tension-related afferent feedback from Golgi tendon organs (Contento et al 2019). Accordingly, we assume that the unchanged MEP amplitudes in our study reflect an increased cortical excitability, which did not contribute to the increased torque production following active muscle stretch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While a reduction in agonist activation is almost certain, it appears to be related, in part, to spinal excitability (Sypkes et al 2018). Contento et al (2019) reported an increased tendonevoked inhibitory reflex during the rFE state compared to strictly isometric contractions. These results likely indicate inhibitory feedback onto the agonist motoneuron pool that is arising from a tension-dependent source within the tendon, most likely the golgi tendon organ, and subsequently reducing spinal excitability (Sypkes et al 2018).…”
mentioning
confidence: 99%